2014
DOI: 10.12691/ajfst-2-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality Evaluation of Composite Bread Produced from Wheat, Maize and Orange Fleshed Sweet Potato Flours

Abstract: The research was carried out to evaluate the effect of addition of yellow maize (YM) and orange fleshed sweet potato (OFSP) flours on the quality of wheat bread. Maize and sweet potato were processed into flour and mixed with wheat flour for bread production. Five samples of bread were produced and denoted as Samples A to E. Sample A was the control with 100% wheat flour, while Sample B to E had maize and sweet potato flours added in an increasing order of 5 to 20%. The physical properties of the bread loaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
38
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 22 publications
11
38
3
Order By: Relevance
“…According to Van Jaarsveld et al, (2005) the sources of pro-vitamin A are fruits and vegetables which are yellow and orange, and dark green leafy vegetables. Orange-fleshed sweet potato tuber is one of beta carotene source (Eluagu & Oniwamo, 2010), which contains 20-30 times more β-carotene than brown rice (Woolfe, 1992). The levels of β-carotene contained in the tubers orange-fleshed sweet potato is higher than the yellow and white tuber flesh colour (Sebuliba et al, 2001).…”
Section: Accessionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Van Jaarsveld et al, (2005) the sources of pro-vitamin A are fruits and vegetables which are yellow and orange, and dark green leafy vegetables. Orange-fleshed sweet potato tuber is one of beta carotene source (Eluagu & Oniwamo, 2010), which contains 20-30 times more β-carotene than brown rice (Woolfe, 1992). The levels of β-carotene contained in the tubers orange-fleshed sweet potato is higher than the yellow and white tuber flesh colour (Sebuliba et al, 2001).…”
Section: Accessionmentioning
confidence: 99%
“…According to Woolfe (1992), orange and yellow sweet potato tubers contains β-carotene up to 4,000 mg 100 g -1 (in the basic of fresh tuber), while the content of β-carotene in white-fleshed sweet potato tubers is less than 70 mg 100 g -1 . The intensity of the orange color is produced by carotenoids (Ameny & Wilson, 1997) which is a pro-vitamin A and also act as antioxidants to fight free radical.…”
Section: Accessionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ash content was one of total solid that effected by activity of starters. According to the connection observed by Bibiana et al (2014), ash content of yoghurt ranged from 0.41% to 1.02%, yoghurt with higher of ash content indicated that yoghurt was better source of minerals. Ladokun and Oni (2014) stated that mineral compositions of milk could be measure with ash content analysis.…”
Section: Ash Contentmentioning
confidence: 92%